The Efficiency of Automated Control Microprocessor Systems for LED Irradiation Installations - N. P. Kondratieva; R. I. Korepanov; I. R. Ilyasov; R. G. Bolshin; M. G. Krasnolutskaya; Ye. N. Somova; M. G. Markova (Сельскохозяйственные машины и технологии, 2018)
Crop productivity is significantly affected by the dose of optical radiation. In particular, southern crops do not have enough time to ripen in a temperate climate because of decreased daylight duration. In conditions of protected soil due to low irradiance and a short daylight duration in autumn-winter months, the cultivation of fully developed plants is possible only with the use of artificial radiation sources. The use of LED phytoinstallations with the help of microprocessorbased automatic control systems allows obtaining the required dose of optical radiation. (Purpose of research) To substantiate, as exemplified by meristematic grape plants, the effectiveness of LED phytoinstallations and their impact on the increase in the leaf surface area; to develop multicolored LED phytoinstallations; to offer new technical solutions to improve the efficiency of the microprocessor system of automatic control of LED phytoinstallations. (Materials and methods) the authors have carried out experiments with meristematic grape plants of RF48 variety (in vitro) at the stages of their rooting and adaptation. The following equipment has been used: LED phytoirradiator with a changing spectrum using a microprocessor control system, “blinking” led phytoirradiator, multicolored phytoiradiator with the addition of UV LEDs. The authors have developed on the basis of microcontroller Arduino uno a microprocessor dispensing system of the spectral components of the areas of the photosynthetically active radiation to automatically control the operation of LEDbased phytoinstallations. (Results and discussion) it has been shown that a LED irradiator with a changing spectral composition, as compared to a luminescent irradiator, at the stage of rooting of grape microsprouts contributes to a significant increase in the leaf surface area of microplants at 100 percent rooting of sprouts. The blinking phytoirradiator and the UVLED phytoirradiator, as compared to the fluorescent ones, contributed to an insignificant increase in leaf area of plants at the adaptation stage of grape microplants. (Conclusions) The authors have confirmed the need to further improve the efficiency of the microprocessorbased automatic control system of LED irradiation installations.